Memórias e experiências de imigrantes espanhóis em Bueno Brandão - MG 1960-1990 - Alencar, Andréa da Silva Morais (2009)
The following research here presented refers to the Spanish immigration in Bueno Brandão - MG. Workers originally from Spain have been interviewed, who arrived in Brazil in the 50 s and have been residents in the city of Bueno Brandão since 1963. Evaluating the social and cultural lives of these subjects are the main purposes of the study that searches an historical interpretation, which may give social visibility to the narrations and life experiences of these witnesses.The methodology used to develop the research is a practice of Oral History, through the statements of common people that guard until today the remembrances of the country of origin. The motives for their social displacement from Spain to Brazil were analyzed, also their routes and journeys up to their arrival in Bueno Brandão, their participations in the growth of the city, in the construction of historical contexts and the remembrances that detach the cultural practices in the country of origin and in Brazil